Religious engineering: exploring projects of transformation from a relational perspective - Spies, Eva (Religion, 2021)
This introduction presents the concept of religious engineering, offering a new perspective on a field of research which deals with the interrelations of religion and international development. The concept, we propose, allows for an analysis of a wide array of projects of transformation without presupposing religion, secularity and development as different given spheres or concepts. Following criticisms of the instrumental use of a sui generis concept of religion and a narrow definition of development, we suggest a focus on the relational, on-going constitution of development and religion through transformative practices of religious engineering. This refers to ways of working on the future shape of a society, group or individual, where the ‘engineers’ allude to what they understand as religious traditions and practices. At the same time, the concept accesses purposeful transformations of religious traditions and self-understandings that are spurred on by such projects of societal and/or individual improvement.